The observed guard dogs’ behaviour towards their own species, farm animals, farm persons and others. - Konstanze Krueger (6750239) (2025)
The behaviour of 19 guard dogs was observed when they were guarding goats and horses at their farms and was categorized as 1) friendly, 2) neutral, 3) anxious, and 4) dominant. The dogs showed significant less anxious behaviour (a) than behaviour from any other category (b; Wilcoxon signed rank tests: N = 19, all p < 0.004).